2019
DOI: 10.1097/pas.0000000000001243
|View full text |Cite
|
Sign up to set email alerts
|

BCOR Overexpression in Renal Malignant Solitary Fibrous Tumors

Abstract: BCOR immunoreactivity is a sensitive and highly specific marker for clear cell sarcoma of the kidney (CCSK). However, a subset of adult renal sarcomas which overexpress BCOR are negative for BCOR genetic alterations, including BCOR gene fusions or BCOR-internal tandem duplication, and thus remain unclassified. We report five such undifferentiated renal/perirenal sarcomas which raised the differential diagnosis of CCSK due to their morphologic appearance and strong BCOR immunoreactivity, but which on RNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…Rather, 90% of CCSK patient samples carry internal tandem duplications (ITDs) in BCOR, which plays essential roles in epigenetic silencing (Astolfi et al, ; Roy et al, ; Ueno‐Yokohata et al, ). Subsequent studies have also described a gene fusion of BCOR with Cyclin B3 (CCNB3), a positive regulator for cyclin‐dependent kinase and cell cycle control, resulting from inv(X)(p11q11), an X chromosomal pericentric inversion in CCSK samples (Argani et al, , ; Kao et al, ). Interestingly, BCOR‐ITD overexpression is also not exclusive to CCSK, and is described in other neoplasms, such as renal malignant solitary fibrous tumor, and high‐grade uterine sarcoma, suggesting its role as potential oncogene and implying that lessons learned in those diseases may also be applicable to CCSK (Argani et al, ; Mariño‐Enriquez et al, ).…”
Section: Clear Cell Sarcoma Of the Kidney: The Second Most Common Chimentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, 90% of CCSK patient samples carry internal tandem duplications (ITDs) in BCOR, which plays essential roles in epigenetic silencing (Astolfi et al, ; Roy et al, ; Ueno‐Yokohata et al, ). Subsequent studies have also described a gene fusion of BCOR with Cyclin B3 (CCNB3), a positive regulator for cyclin‐dependent kinase and cell cycle control, resulting from inv(X)(p11q11), an X chromosomal pericentric inversion in CCSK samples (Argani et al, , ; Kao et al, ). Interestingly, BCOR‐ITD overexpression is also not exclusive to CCSK, and is described in other neoplasms, such as renal malignant solitary fibrous tumor, and high‐grade uterine sarcoma, suggesting its role as potential oncogene and implying that lessons learned in those diseases may also be applicable to CCSK (Argani et al, ; Mariño‐Enriquez et al, ).…”
Section: Clear Cell Sarcoma Of the Kidney: The Second Most Common Chimentioning
confidence: 99%
“…Subsequent studies have also described a gene fusion of BCOR with Cyclin B3 (CCNB3), a positive regulator for cyclin‐dependent kinase and cell cycle control, resulting from inv(X)(p11q11), an X chromosomal pericentric inversion in CCSK samples (Argani et al, , ; Kao et al, ). Interestingly, BCOR‐ITD overexpression is also not exclusive to CCSK, and is described in other neoplasms, such as renal malignant solitary fibrous tumor, and high‐grade uterine sarcoma, suggesting its role as potential oncogene and implying that lessons learned in those diseases may also be applicable to CCSK (Argani et al, ; Mariño‐Enriquez et al, ). Additionally, a chromosomal translocation affecting t(10;17)(q22;p13), resulting in a YWHAE‐NUTM2B fusion, is strongly implicated as the primary initiating pathogenic event for 5% of CCSK (O'meara et al, ; Punnett, Halligan, Zaeri, & Karmazin, ; Rakheja et al, ; Table ).…”
Section: Clear Cell Sarcoma Of the Kidney: The Second Most Common Chimentioning
confidence: 99%
“…The NAB2–STAT6 fusion is the molecular hallmark (Fig. d) of SFTs . Although Barthelmess et al detected a significant association between the NAB2ex6‐ STAT6ex16/17 variant and malignancy in SFTs, other authors have reported that no fusion variants are associated with malignancy …”
Section: Introductionmentioning
confidence: 97%
“…Many of the histological variants reveal a focal patternless architecture, and variably fibro‐collagenous stroma . NAB2‐STAT6 was discovered as a novel fusion gene of SFTs, and STAT6 immunoexpression has been established as a surrogate marker of the NAB2‐STAT6 gene fusion, expression of this protein representing a very sensitive and specific diagnostic tool …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation